Penerimaan Vaksinasi Corona Virus Disease-19 Pada Masyarakat di Kota Manado: Studi Deskriptif - Shania Nonutu; Jeini Ester Nelwan; Grace Debbie Kandou (Sam Ratulangi Journal of Public Health, 2024)
Background: The Coronavirus Disease-19 (COVID-19) pandemic situation has had an impact on various aspects. One of them is health services which are proven by a decrease in the number of patients, modification of services by health workers, changes in the use of hospital facilities and infrastructure and psychological impacts and other aspects in the community. The purpose of this study is to describe the factors of receiving the Coronavirus Disease 2019 vaccination in the community in Manado City. Methode: This is descriptive quantitative research. The sample in this study is all people aged 18 years and above who are domiciled in Ranotana, Sario District. The number of samples in this study is 278 samples, Proportional Sampling technique with criteria of ≥18 years old and willing to be a respondent. The data obtained was then analyzed descriptively. Results: The results showed that the most respondents were distributed at the age of 26-45 years as much as 49.6%, the equivalent of university education as much as 57.6%, the knowledge of answering correctly on the statement about COVID-19 vaccination has been clinically tested so that it is safe and halal to use as much as 18.5%, the attitude of the most respondents who answered strongly agrees with continuing to implement health protocols even though they have received the vaccine as much as 15.8% and the most Christian beliefs Protestants as many as 85.2%. Conclusion: It can be concluded that the people in Manado city are at most 26-45 years old, university education and equivalent, knowledge about COVID-19 vaccination has been clinically tested so that it is safe and halal to use, attitude about continuing to implement health protocols even though they have received the vaccine and are Protestant Christians.